Dosimetric impact of gold markers implanted closely to lung tumors: a Monte Carlo simulation. (8th May 2014) - Shiinoki, Takehiro; Sawada, Akira; Ishihara, Yoshitomo; Miyabe, Yuki; Matsuo, Yukinori; Mizowaki, Takashi; Kokubo, Masaki; Hiraoka, Masahiro
Abstract : We are developing an innovative dynamic tumor tracking irradiation technique using gold markers implanted around a tumor as a surrogate signal, a real‐time marker detection system, and a gimbaled X‐ray head in the Vero4DRT. The gold markers implanted in a normal organ will produce uncertainty in the dose calculation during treatment planning because the photon mass attenuation coefficient of a gold marker is much larger than that of normal tissue. The purpose of this study was to simulate the dose variation near the gold markers in a lung irradiated by a photon beam using the Monte Carlo method. First, the single‐beam and the opposing‐beam geometries were simulated using both water and lung phantoms. Subsequently, the relative dose profiles were calculated using a stereotactic body radiotherapy (SBRT) treatment plan for a lung cancer patient having gold markers along the anteriorposterior (AP) and right‐left (RL) directions. For the single beam, the dose at the gold marker‐phantom interface laterally along the perpendicular to the beam axis increased by a factor of 1.35 in the water phantom and 1.58 in the lung phantom, respectively. Furthermore, the entrance dose at the interface along the beam axis increased by a factor of 1.63 in the water phantom and 1.91 in the lung phantom, while the exit dose increased by a factor of 1.00 in the water phantom and 1.12 in the lung phantom, respectively. On the other hand, both dose escalations and dose de‐escalations were canceled by each beam for opposing portal beams with the same beam weight. For SBRT patient data, the dose at the gold marker edge located in the tumor increased by a factor of 1.30 in both AP and RL directions. In clinical cases, dose escalations were observed at the small area where the distance between a gold marker and the lung tumor was ≤ 5 mm, and it would be clinically negligible in multibeam treatments, although further investigation may be required. PACS number: 87.10.Rt